Attitude change revisited cognitive dissonance theory and development policy - James, Jeffrey; Gutkind, Efraim (Pergamon Press Ltd., 1985)
This paper extends earlier work done by Hirschman on the potential usefulness of cognitive dissonance theory for explaining the process of attitude change in the course of economic development. According to this theory attitude change may follow rather than precede a change in behavior. The paper shows that an examination of the specific conditions under which this may occur can throw light on the success and failure of particular development policies. Successful outcomes appear to have been produced by policies that paid close attention to the subtle psychological requirements for effecting counter-attitudinal behavior with a minimum amount of perceived pressure.